Confronting Racism in Novel " An American Marriage " by Tayari Jones (2018) - Sadena, Caneffy; Al-Hafizh, Muhammad (English Language and Literature, 2024)
This research is an analysis of the Novel “An American Marriage” by Tayari Jones (2018). In this study, the author aims to reveal the racism effect in American marriage life . In analysis, there are 3 form of racism, 2 impact of racism, and 2 type of how to confront the racism. This analysis uses Post Colonial theory to reveal the forms, impact ,and confront racism and using observations and analytical methods. The forms of racism in this thesis is racial slurs, discrimination, and violence. The impact of racism in this thesis are psychological and physical. The resistance towards racism in this thesis includes education awareness and building relationship. The use of concept based on the context of the novel in this analysis, the element of novel that help reveal the implied meaning are tone, speaker, and symbol. In conclusion, in this thesis , author aims to reveal racism, the impact of racism and how to confront racism in the novel “An American Marriage” by Tayari Jones (2018).